2021
DOI: 10.1111/bcpt.13631
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure requiring transplantation: A possible link to ulipristal acetate treatment?

Abstract: The present case describes in detail a 55‐year‐old woman diagnosed with acute liver injury 3 days after completion of the first treatment course with ulipristal acetate (UPA), 5 mg/day orally for uterine fibroids causing persistent bleeding (treatment duration of 109 days). Liver transplantation was performed approximately 6 weeks after UPA suspension, and a photograph of the explanted liver is presented. Of note, other common causes of acute liver injury, such as history of alcohol or other psychoactive subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Another study reported frequent adverse symptoms and a higher rate of treatment discontinuation in women with adenomyosis or uterine leiomyomas [ 81 ]. Additionally, sporadic cases of liver injury and liver failure were reported during post-marketing experience, which decrease the UPA use worldwide [ 82 , 83 ]. Therefore, healthcare professionals should provide comprehensive information about the potential incidence of adverse symptoms to women considering ulipristal acetate treatment.…”
Section: The Role Of Medical Therapy For Treating Symptoms Related To...mentioning
confidence: 99%
“…Another study reported frequent adverse symptoms and a higher rate of treatment discontinuation in women with adenomyosis or uterine leiomyomas [ 81 ]. Additionally, sporadic cases of liver injury and liver failure were reported during post-marketing experience, which decrease the UPA use worldwide [ 82 , 83 ]. Therefore, healthcare professionals should provide comprehensive information about the potential incidence of adverse symptoms to women considering ulipristal acetate treatment.…”
Section: The Role Of Medical Therapy For Treating Symptoms Related To...mentioning
confidence: 99%
“…These results implied that our model had a good predictive performance to accurately identify DILI drugs. [27] 5,493,444 7.0% DILI-positive 0.999 Rilpivirine [28] 6,451,164 5.0% DILI-positive 0.994 Escitalopram [29] 146,570 5.0% DILI-positive 0.989 Nilotinib [30] 644,241 7.6% DILI-positive 0.982 Olmesartan [31] 158,781 6.3% DILI-positive 0.974 Mesterolone [32] 15,020 4.1% DILI-positive 0.971 Levothyroxine [33] 5819 3.9% DILI-positive 0.965 Zanubrutinib [34] 135,565,884 6.4% DILI-positive 0.922 Phenprobamate [35] 4770 2.8% DILI-positive 0.896 Apixaban [36] 10,182,969 5.5% DILI-positive 0.804 Fasiglifam [37] 24,857,286 7.0% DILI-positive 0.660 Pirfenidone [38] 40,632 2.6% DILI-positive 0.608 Ligandrol [39] 44,137,686 4.6% DILI-negative 0.378 Ulipristal acetate [40] 130,904 6.5% DILI-negative 0.036 DILI, drug-induced liver injury.…”
Section: Dili Prediction On Drugs That Have Case Reports On Liver Injurymentioning
confidence: 99%